Papież - święty z definicji? Od Dictatus papae do Santo subito - Grzeszczak, Jan (Poznańskie Studia Teologiczne, 2010)
The study of an Italian historian of Christianity Roberto Rusconi: Santo Padre. La santità del papa de san Pietro a Giovanni Paolo II (Holy Father. Holiness of a pope from St Peter to John Paul II) is the first attempt of showing in what way throughout history there was presented holiness of a pope in Church. In this detailed monograph a reader will find not only the presentation of holy popes, from Apostolic times till the XX century, but above all the presentation of the problem of holiness relating to the highest post in Church. Studies of Rusconi cast in this way a new light on the history of Church, religiosity and the process of formal acknowledgement of holiness within the space of centuries. In his study Roberto Rusconi claims that the twenty third statement of Dictatus papae of Pope Gregory VII (1073-1085): Romanus pontifex, si canonice fuerit electus, meritis beati Petri indubitanter efficitur sanctus (the Roman pontiff, if he have been canonically ordained, is undoubtedly made a saint by the merits of St Peter) has been fulfilled these days, being this way a kind of a prophecy. The author comes to such a conclusion analysing the evolution of perceiving the figure of a pope and his holiness, especially in the last two centuries, and also the fact that there have already been beatified or there have been opened processes of beatification of all the popes of the last half-century.